2023
DOI: 10.1111/cas.15773
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell RNA sequencing reveals tumor heterogeneity, microenvironment, and drug‐resistance mechanisms of recurrent glioblastoma

Abstract: Glioblastomas are highly heterogeneous brain tumors. Despite the availability of standard treatment for glioblastoma multiforme (GBM), i.e., Stupp protocol, which involves surgical resection followed by radiotherapy and chemotherapy, glioblastoma remains refractory to treatment and recurrence is inevitable. Moreover, the biology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Conventional scRNA-seq technologies encounter limitations when attempting to utilize matched primary-recurrent samples from the same patients for longitudinal clinical study 37 . This limitation can potentially result in the omission of crucial information regarding tumor progression.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional scRNA-seq technologies encounter limitations when attempting to utilize matched primary-recurrent samples from the same patients for longitudinal clinical study 37 . This limitation can potentially result in the omission of crucial information regarding tumor progression.…”
Section: Resultsmentioning
confidence: 99%
“…2 A, B) raises an intriguing question as to whether the molecular transition seen in rGBM cells is attributed to the change of the whole population of tumor cells or preferentially a subset of cells, which cannot be fully addressed by bulk sample data [ 42 ]. On the other hand, the heterogeneity of rGBM cells has just begun to be studied and how tumor cells at recurrence behave differently is incompletely understood [ 15 , 24 , 42 , 59 ]. To tackle the above question and explore the heterogeneity of rGBM, we retrieved the GBM cells across the longitudinal samples and performed clustering analysis according to their transcriptomic similarity.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies reported several cellular and molecular changes at GBM recurrence, such as mesenchymal transition with decreased proneuronal state, increased proportion of oligodendrocytes, and enriched ECM signatures, revealing a systematic context shift of the tumor and neighborhood [ 14 17 , 23 , 24 , 59 , 76 ]. Thus, the comprehensive characterization of rGBM tissues in comparison to pGBM is indispensable for understanding the molecular mechanism of relapse and searching specific therapeutic targets [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the aforementioned evidence, EVs appear to be fundamental in understanding glioma interplay with the microenvironment. However, they appear to be heterogeneous, like the several cell populations found in tumor tissue [10,121]. Profiling the EVs based on the cells of origin would provide insights into elucidating the molecular content and the interactions occurring between human glioma, astrocytes, and myeloid cells.…”
Section: Methodsmentioning
confidence: 99%